THE EFFECTIVENESS OF DIRECT INTERACTION MODEL–ASSISTED MACROMEDIA FLASH ON COLLIGATIVE PROPERTIES OF SOLUTIONS MATERIAL - Fatayah, Fatayah; Purwanto, Kriesna Kharisma (Universitas Negeri Surabaya, 2019)
Abstract. The purpose of this study was to determine the effectiveness of the use of direct instruction model-assisted macromedia flash. The effectiveness of the learning model are measured by two indicators, that are the activities of students during learning and the level of completeness of student learning outcomes after learning activities. From the analysis of the data it is known that the activities of students during learning are at scores 4 and 5, the average cognitive score of students is 78 and the lowest score was 76. From the results of this study it can be concluded that the application of direct instruction model based on macromedia flash is effective to reduce student learning difficulties Class XII IPA MA Al-Khoiriyah Dalegan Panceng on the colligative properties of the solutions material.Â Keywords: effectiveness, direct instruction model, macromedia flash, colligative properties of solutions